2012
DOI: 10.1248/bpb.b12-00505
|View full text |Cite
|
Sign up to set email alerts
|

Possible Involvement of Hypothalamic Nucleobindin-2 in Hyperphagic Feeding in Tsumura Suzuki Obese Diabetes Mice

Abstract: The aim of this study was to clarify the hypothalamic neuropeptides that are associated with hyperphagic feeding in Tsumura Suzuki Obese Diabetes (TSOD) mice, a model of type 2 diabetes with polygenic abnormalities. TSOD mice showed an increase in body weight and hyperleptinemia from 1 month of age and hyperphagic feeding, hyperglycemia, hyperlipidemia and hyperinsulinemia from 3 to 12 months of age compared with age-matched non-diabetic control Tsumura Suzuki Non Obesity (TSNO) mice. The mRNA level of nucleob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 56 publications
3
15
1
1
Order By: Relevance
“…1b), indicating that TSOD mice already developed hypercholesterolemia at 5 weeks of age. Although non-fasting blood glucose level in TSOD mice at 11 weeks of age was significantly higher than that in age-matched TSNO mice, as reported previously, (7) no significant difference in glucose level was found between TSNO and TSOD mice at 5 weeks of age (Fig. 1c).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…1b), indicating that TSOD mice already developed hypercholesterolemia at 5 weeks of age. Although non-fasting blood glucose level in TSOD mice at 11 weeks of age was significantly higher than that in age-matched TSNO mice, as reported previously, (7) no significant difference in glucose level was found between TSNO and TSOD mice at 5 weeks of age (Fig. 1c).…”
Section: Resultssupporting
confidence: 85%
“…1a), consistent with a previous report. (7) Weight gain in TSOD mice during the period between 5 and 11 weeks of age was much greater than that in TSNO mice during the same period, indicating that the progression of obesity is rapid in TSOD mice compared with TSNO mice. Whereas plasma total cholesterol levels in TSOD mice at 5 and 11 weeks of age were significantly higher than those in age-matched TSNO mice, no significant difference was observed between TSOD mice at 5 and 11 weeks of age (Fig.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…In rodents, fasting decreased NUCB2/nesfatin-1 expression in the PVN [3], whereas refeeding increased the number of nesfatin-1-immunopositive neurons and NUCB2 mRNA in the SON [31]. Miyata et al [32] have reported that hypothalamic NUCB2 mRNA and protein levels were significantly reduced in mouse obesity models compared to controls. However, it is unknown whether such an association exists in humans.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is supported by the observation that TSOD mice dramatically gain weight around 5 weeks of age and the rate of weight gain is similar to that of TSNO mice after 5 weeks of age. 10,29) In the period, obesity is mainly developed by overeating which is caused by hypothalamic neuropeptides and the properties of adipocytes may syner- gistically promote the development of obesity. It will lead to development of T2DM.…”
Section: Discussionmentioning
confidence: 99%